INDONESIA’S PUBLIC DIPLOMACY THROUGH THE AQUABIKE JETSKI WORLD CHAMPIONSHIP LAKE TOBA 2023–2024 - Mochamad Agil Syiraj; Muhammad Indrawan Jatmika; Reyhan Javier Barrulanda (Journal Publicuho, 2025)
This study analyses Indonesia's public diplomacy practices through the organisation of the Aquabike Jetski World Championship held in Lake Toba, North Sumatra. As part of the Super Priority Tourism Destinations, Lake Toba holds strategic value not only for promoting local culture but also for strengthening Indonesia's image as a capable host of international sporting events. This event serves as a medium for Indonesia to present itself to the global public while simultaneously asserting its strategic position in international political dynamics through sports. The study employs a descriptive qualitative approach with data collected through a literature review. The analysis is grounded in Nicholas J. Cull’s concept of public diplomacy, particularly focusing on three main elements: listening, advocacy, and international broadcasting. The findings reveal that through the implementation of this event, Indonesia actively applies public diplomacy strategies aimed at building a positive national image and enhancing its visibility on the global stage.